Thirteen ways of looking at HDB windows - Tan, Yi Xin (2018)
Thirteen Ways of Looking at HDB Windows is a short story collection exploring the relationship between the HDB window and its residents, in terms of how windows inform the interactions between individuals in a community and also affect the habits and life stories of residents. This project consists of thirteen short stories set within the Ghim Moh Road HDB estate, or more specifically, Blocks 14 and 15 of said estate.